Can Peripheral Gentral Venous Lines be inserted safely and successf ully where X-ray facilities are no available? - J.M. Boon; R.E. Kirby (South African Family Practice)
Background: Primary care settings often lack facilities for radiological evaluation of the position of supra-and infra-clavicularly inserted central Yenous catheters' lf peripherally inserted central venous lines could reliably be successfully inserted this would make the need for immediate confirmatory radiological studies less crucial. Previous studies with peripherally inserted catheters reported a low success rate.This study was performed to determine whether the placement of a more flexible peripherally inserted catheter, the Arrow PICC (Arrow PS-O165 l), would result in an improved and acceptable success rate.